2007
DOI: 10.1128/jvi.00274-07
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vaccinia Virus Fusion Regulatory Proteins with the Multicomponent Entry/Fusion Complex

Abstract: The proteins encoded by the A56R and K2L genes of vaccinia virus form a heterodimer (A56/K2) and have a fusion regulatory role as deletion or mutation of either causes infected cells to form large syncytia spontaneously. Here, we showed that syncytia formation is dependent on proteins of the recently described entry fusion complex (EFC), which are also required for virus-cell fusion and low-pH-triggered cell-cell fusion. This finding led us to consider that A56/K2 might prevent fusion by direct or indirect int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 42 publications
3
72
0
Order By: Relevance
“…Taken together, these results indicate that VCP and A56 interact in infected cells. Of note, Wagenaar and Moss recently used tandem affinity purification and mass spectrometry to identify proteins that interact with A56 (45). Their study identified VCP as one of many proteins that copurifies with A56, lending support to our finding that these two proteins interact.…”
Section: Vol 82 2008 Expression Of Vcp On Vaccinia Virus-infected Csupporting
confidence: 71%
“…Taken together, these results indicate that VCP and A56 interact in infected cells. Of note, Wagenaar and Moss recently used tandem affinity purification and mass spectrometry to identify proteins that interact with A56 (45). Their study identified VCP as one of many proteins that copurifies with A56, lending support to our finding that these two proteins interact.…”
Section: Vol 82 2008 Expression Of Vcp On Vaccinia Virus-infected Csupporting
confidence: 71%
“…Deletion or mutation of either of these proteins results in the formation of syncytia at neutral pH (62)(63)(64)(65)(66). The finding that the A56/K2 heterodimer interacts specifically with two interacting proteins of the EFC provided a mechanism for preventing syncytium formation (7,8). Turner and Moyer (5) reported that cells infected with A56 or K2 mutants have increased susceptibility to superinfection at late times.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded, mainly based on UV inactivation of virus particles, that early gene expression by the primary virus was responsible for resistance to superinfection and that early gene expression by the secondary virus was prevented. Subsequent studies provided evidence that SIE can be mediated by a heterodimer formed by the A56 and K2 proteins on the cell membrane (5, 6), which interact with a protein complex on the virus surface that is required for fusion and entry (7,8). Whether this mechanism, which was demonstrated at a late phase of virus replication, is related to the early SIE was not assessed.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…A serine protease inhibitor (SPI-3) encoded by K2 depends on the association with A56 for membrane localization (166). By direct interaction with the poxvirus EFC, the A56/K2 complex prevents virus entry and fusion and likely mediates the phenomenon of superinfection exclusion (167)(168)(169)(170). Additional viral PPI studies have shown that both A16 and G9, which are physically associated within the EFC, are required for binding to A56/K2 (170).…”
Section: Virus-virus Protein Interactionsmentioning
confidence: 99%